YOGURT PRODUCT DESIGN BY USING QUALITY FUNCTION DEPLOYMENT: A CONCEPTUAL FRAMEWORK - Arief Rahmawan; Novia Nur Rosyida (Jurnal Agroindustri, 2018)
University of Darussalam Gontor is a higher education institution which has Agro-Industrial Technology Department. As a department with mission to create Moslem technopreneur, student business unit is created as laboratory to produce vary agroindustry products, and yogurt YoFresh is one of their main products. Quality function deployment is one of the most important developed tools to ensure the quality of product and service. As an emerging business unit in agro-industrial technology department, QFD methodology is attempted to propose design characteristic of yogurt and match with voice of customer. This research is proposed to improve the quality and product design of product developed student business unit in Agro-Industrial Technology Department. This research consists of three stages by utilize QFD application, which are: (1) determine the voice of customer (2) determine of technical responses and (3) relationships between both stages. As the beginning, voice of customer identification is paramount as input of QFD application. Furthermore, identifying product characteristic by conducting interview with management of YoFresh is necessary in order to obtain technical response as the sub-matrix of QFD. To complete QFD analysis, relationships between previous stages is analyzed to obtain the score of technical responses. Results from this research will evaluate and give blossom opportunities for innovative agroindustry products. The more variative agroindustry products created, the more insight and experience for students to have. Through business unit, agroindustry department of UNIDA Gontor will successfully deliver the value of moslem technopreneur.